Water-Conserving and Runoff-Reducing Production Systems for Containerized Plants: Some Examples of Recently Developed Technologies - Sharma Jyotsna; Dorota Z. Haman; Richard C. Beeson, Jr. (EDIS)
ENH-1048, a 6-page illustrated fact sheet by Sharma, J., Haman, D.Z., and Beeson, Jr., R.C., describes some new, water conserving production systems for containerized plant production in outdoor nurseries that use the concepts of micro-irrigation and subirrigation. Includes references. Published by the UF Department of Environmental Horticulture, December 2006.